POPULASI VEKTOR DEMAM BERDARAH DENGUE DI DAERAH RURAL KOTA SEMARANG : CROSSECTIONAL SURVEY BIONOMIK AEDES sp - Sri Yuliawati; Dewi Fajar Kharisma; Martini Martini; Lintang Dian Saraswati; Retno Hestiningsih; Susiana Purwantisari (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Dengue Hemorrhagic Fever (DHF) caused by dengue virus transmitted by Aedes sp. Population of Aedes sp needed to know bionomic and ecologic especially in rural areas. This study aims to determine the Aedes sp density description at the Rowosari village, Tembalang Sub-district, Semarang City. This is descriptive research using cross sectional approach that conducted by survey and observation method about the density of Aedes sp. The study sample are 100 houses spreading in each sub village in Rowosari selected by the purposive sampling method. The results show the density of larvae in Rowosari is very high based on larvae density index HI = 44.1%, CI = 31,7%, BI =74,9% OI= 64,1%, so it can be said Rowosari including areas with high risk of dengue. The Aedes aegypti density is 0.67 resting inside house and 0 resting outside house. The Aedes albopictus density 0.13 resting inside house and 0,06 resting outside house. During the study founded 2 types of Aedes sp that are Aedes aegypti (53%) and Aedes albopictus (4.7%). Based on this research, suggest to use the type of container that mosquitoes doesn’t prefer for breeding place and routinely clean the containers either in house and outside the house.Keywords: DHF, Aedes sp, Aedes albopictus, Larvae Density, DBD